PENGARUH IKLIM BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS XI AKUNTANSI DI SMKN 3 PONTIANAK - Azis, Abdul; Asriati, Nuraini; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThisÂ  is titled "The Effect of School Learning Climate on Student Learning Outcomes of Class XI AK on Accounting System Material in SMK Negeri 3 Pontianak". This study aims to determine the Effect of School Learning Against Student Learning Outcomes of Class XI AK on Accounting System Material at SMK Negeri 3 Pontianak . The research method used in this study is quantitative. The results of this study: 1) Learning Climate in SMK Negeri 3 Pontianak, for learning climate included in both categories that can be seen from the results of the study climate study that is 72.88% or 43 of 59 respondents who choose the answer in either category.2). Class XI AK student learning outcomes on accounting system material in SMK Negeri 3 Pontianak, for learning outcomes (variable Y) Class XI AK students on accounting system material at SMK Negeri 3 Pontianak included in the good category that the value of 77.444 is included in the good category, thus the results student learning in the good category this is due to the good student learning climate pulak, where students can receive learning well in accordance with the value of completeness.3) The magnitude of the influence of the learning climate (X) on student learning outcomes (Y) class XI AK on subjects accounting at SMK Negeri 3 Pontianak by 33.2% with a coefficient of determination of 0.425 and the level of interpretation of the relationship is moderate.Keywords: Study Climate, Learning Outcomes and Subjects Accounting System